The potential of IFN-λ, IL-32γ, IL-6, and IL-22 as safeguards against human viruses: a systematic review and a meta-analysis - Sattar, Areej A.; Qaiser, Ariba; Kausar, Hina; Aqil, Sarah; Mudassar, Rida; Manzoor, Sobia; Ashraf, Javed (Frontiers in Immunology, 2024)
Many studies have investigated the antiviral activity of cytokines, including Interleukin 6 (IL- 6), Interleukin 22 (IL-22), Interleukin 32 gamma (IL-32 γ), and Interferon-Lambda (IFN-λ) in diverse populations. This study aims to evaluate the role of these cytokines in inhibition of various human and animal viruses when administered exogenously. A comprehensive meta-analysis and systematic review were conducted on all the relevant studies from three databases. Standard Mean Differences (SMD) of overall viral inhibition, were used to generate the difference in the antiviral efficacy of these cytokines between control and experimental groups. A total of 4618 abstracts for IL-6, 3517 abstracts for IL-22, 2160 abstracts for IL-32 γ, and 1026 abstracts for IFN-λ were identified, and 7, 4, 8, and 35 studies were included respectively for each cytokine. IFN-λ (SMD= 0.9540; 95% CI: 0.69-0.22) and IL-32γ (SMD= 0.459; 95% CI: 0.02-0.90) showed the highest influence followed by IL-6 (SMD= 0.456; CI: - 0.04-0.95) & IL-22 (SMD= 0.244; 95% CI: -0.33-0.81). None of the cytokines represented heterogeneity (tau² > 0), but only IFN-λ indicated the funnel plot asymmetry (p = 0.0097). Results also indicated that IFN-λ and IL-32 γ are more potent antivirals than IL-6 and IL-22. The collective findings of this study emphasize that exogenously administered proinflammatory cytokines, specifically IFN-λ and IL-32, exhibit significant antiviral activity, thereby underscoring them as potent antiviral agents. Nonetheless, additional research is required to ascertain their clinical utility and potential for integration into combinatorial therapeutic regimens against viral infections.